The role of the pre-commissural fornix in episodic autobiographical memory and simulation. (May 2020) - Williams, Angharad N.; Ridgeway, Samuel; Postans, Mark; Graham, Kim S.; Lawrence, Andrew D.; Hodgetts, Carl J.
Abstract: Neuropsychological and functional magnetic resonance imaging evidence suggests that the ability to vividly remember our personal past, and imagine future scenarios, involves two closely connected regions: the hippocampus and ventromedial prefrontal cortex (vmPFC). Despite evidence of a direct anatomical connection from hippocampus to vmPFC, it is unknown whether hippocampal-vmPFC structural connectivity supports both past- and future-oriented episodic thinking. To address this, we applied a novel deterministic tractography protocol to diffusion-weighted magnetic resonance imaging (dMRI) data from a group of healthy young adult humans who undertook an adapted past-future autobiographical interview (portions of this data were published in Hodgetts et al., 2017a). This tractography protocol enabled distinct subdivisions of the fornix, detected previously in axonal tracer studies, to be reconstructed in vivo, namely the pre-commissural (connecting the hippocampus to vmPFC) and post-commissural (linking the hippocampus and medial diencephalon) fornix. As predicted, we found that inter-individual differences in pre-commissural - but not post-commissural - fornix microstructure (fractional anisotropy) were significantly correlated with the episodic richness of both past and future autobiographical narratives. Notably, these results held when controlling for non-episodic narrative content, verbal fluency, and grey matter volumes of the hippocampus and vmPFC. This study provides novel evidence that reconstructing events from one's personal past, and constructing possible future events, involves a distinct, structurally-instantiated hippocampal-vmPFC pathway. Highlights: Hippocampal-vmPFC interactions critical to a number of memory and imagination functions. Precommissural fornix provides sole route for direct hippocampal-vmPFC connections. Healthy participants completed past-future autobiographical interview and diffusion MRI. Precommissural fornix microstructure linked to episodic content of past and future narratives.